Oral pathogens exacerbate Parkinson’s disease by promoting Th1 cell infiltration in mice - Bai, Xue-Bing; Xu, Shuo; Zhou, Lu-Jun; Meng, Xiao-Qian; Li, Yu-Lin; Chen, Yan-Lin; Jiang, Yi-Han; Lin, Wen-Zhen; Chen, Bo-Yan; Du, Lin-Juan; Tian, Guo-Cai; Liu, Yan; et al. (Microbiome, 2023)
BackgroundParkinson’s disease (PD) is a common chronic neurological disorder with a high risk of disability and no cure. Periodontitis is an infectious bacterial disease occurring in periodontal supporting tissues. Studies have shown that periodontitis is closely related to PD. However, direct evidence of the effect of periodontitis on PD is lacking. Here, we demonstrated that ligature-induced periodontitis with application of subgingival plaque (LIP-SP) exacerbated motor dysfunction, microglial activation, and dopaminergic neuron loss in 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mice.ResultsThe 16S rRNA gene sequencing revealed that LIP-SP induced oral and gut dysbiosis. Particularly, Veillonella parvula (V. parvula) and Streptococcus mutans (S. mutans) from oral ligatures were increased in the fecal samples of MPTP + LIP-SP treated mice. We further demonstrated that V. parvula and S. mutans played crucial roles in LIP-SP mediated exacerbation of motor dysfunction and neurodegeneration in PD mice. V. parvula and S. mutans caused microglial activation in the brain, as well as T helper 1 (Th1) cells infiltration in the brain, cervical lymph nodes, ileum and colon in PD mice. Moreover, we observed a protective effect of IFNγ neutralization on dopaminergic neurons in V. parvula- and S. mutans-treated PD mice.ConclusionsOur study demonstrates that oral pathogens V. parvula and S. mutans necessitate the existence of periodontitis to exacerbate motor dysfunction and neurodegeneration in MPTP-induced PD mice. The underlying mechanisms include alterations of oral and gut microbiota, along with immune activation in both brain and peripheral regions.Video Abstract